2021
DOI: 10.1097/mpg.0000000000003339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe Acute Respiratory Syndrome Coronavirus Type 2 on Children With Liver Diseases

Abstract: Children are seldom affected by severe forms of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV2) infection; however, the impact of comorbidities in the clinical presentation and outcome of SARS-CoV2 in children is poorly characterized including that of chronic liver disease (CLD) and those taking immunosuppressive medications for autoimmune liver disease or following liver transplantation (LT). Although not the main target organ, a spectrum of liver involvement has been described in children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 139 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…According to the European Society for Paediatric Gastroenterology, Hepatology and Nutrition committee, children with CLD are at a higher risk of developing severe COVID-19 and may experience decompensation of end-stage liver disease during SARS-CoV-2 infection. Children with CLD associated with suspected or documented non-alcoholic fatty liver disease or autoimmune hepatitis may have a higher risk of developing severe COVID-19 [ 13 ]. Kehar et al [ 14 ] compared children with CLD with liver transplant recipients and found that children with CLD required more intensive care unit management and had higher mortality than liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Society for Paediatric Gastroenterology, Hepatology and Nutrition committee, children with CLD are at a higher risk of developing severe COVID-19 and may experience decompensation of end-stage liver disease during SARS-CoV-2 infection. Children with CLD associated with suspected or documented non-alcoholic fatty liver disease or autoimmune hepatitis may have a higher risk of developing severe COVID-19 [ 13 ]. Kehar et al [ 14 ] compared children with CLD with liver transplant recipients and found that children with CLD required more intensive care unit management and had higher mortality than liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 , 13 However, over the past two years it has become apparent that this is not the case. 14 , 15 In a multicenter international observational registry including 180 pediatric liver transplant recipients with laboratory confirmed SARS-CoV-2 infection, none of the transplant recipients required mechanical ventilation or died. 15 , 16 In another multicenter observational registry through the Pediatric Heart Transplant Society Registry, of 866 pediatric heart transplant recipients with COVID-19, only 14% required hospitalization, 5% required intensive care unit (ICU) admission, 1% required ventilation and less than 1% died.…”
Section: Introduction On Covid-19mentioning
confidence: 99%
“…7 , 18 As a result, being on chronic immunosuppressive medications may be protective against severe COVID-19. 14 , 15 , 16 , 19 , 20 Calcineurin inhibitors may specifically help to inhibit Coronavirus replication. 21 In a European observational registry including 243 adult liver transplant recipients with laboratory confirmed SARS-CoV-2, tacrolimus use had a positive independent effect on survival (HR, 0.55; 95% CI, 0.31-0.99).…”
Section: Introduction On Covid-19mentioning
confidence: 99%
See 2 more Smart Citations